FORMATION OF THE TRAIT-SPECIFIC GROUP IN VIR'S TABLE BEET COLLECTION: ENVIRONMENTAL PLASTICITY AND STABILITY - D. V. Sokolova (Труды по прикладной ботанике, генетике и селекции)
Background. Information on the characteristics of the reaction of genotypes to different habitat conditions is of great importance for  solving practical problems of breeding. Table beet (Beta vulgaris L.  subsp. vulgaris) has great food significance. It is among the three  most common vegetable crops in Russia and is grown in many  climatic zones. The ecogeographic approach in evaluating VIR's beet  collection accessions is historically justified and mandatory. The  analysis of the genotype-environment interaction makes it possible  to give a comprehensive description to each accession, and reveal its potential capabilities, the level of plasticity, and the habitat.  Estimation of the level of crop yield stability in different soil and  climate zones of cultivation shows the expediency of placing a variety in specific conditions.Materials and methods. Included in the experiment were 21 table  beet collection accessions of five different variety types varying both  in morphological features and in their origin. Evaluation of the  adaptive potential of beet varieties was carried out according to the  statistical parameters calculated on the basis of the crop's root  yields. The account was made according to VIR's Methodical  Guidelines for the evaluation and preservation of the world collection of root crops.Results and conclusion. Testing of a set of table beet accessions  revealed significant variability in their environmental plasticity and  stability, and showed the expediency of their placement in different  agroclimatic zones. Analysis of the data identified the most adaptive  varieties of different types, characterized by the highest yield and  stability in different geographical sites of cultivation. As a result of  the evaluation, a trait-specific group of the most adaptive table beet  varieties with a broad geographic area of distribution was formed: 'Agyptische' (k-642), 'Detroit dark red turnip improved' (k-1757),  'Perfected Detroid Dark Red'(k-1815), and 'Prygaruzhnya' (k-3064).  The identified accessions of table beet can be recommended for use as source material for breeding for adaptability.